2020
DOI: 10.1093/bib/bbaa233
|View full text |Cite|
|
Sign up to set email alerts
|

Systemic effects of missense mutations on SARS-CoV-2 spike glycoprotein stability and receptor-binding affinity

Abstract: The spike (S) glycoprotein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is responsible for the binding to the permissive cells. The receptor-binding domain (RBD) of SARS-CoV-2 S protein directly interacts with the human angiotensin-converting enzyme 2 (ACE2) on the host cell membrane. In this study, we used computational saturation mutagenesis approaches, including structure-based energy calculations and sequence-based pathogenicity predictions, to quantify the systemic effects of missense m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
105
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(108 citation statements)
references
References 37 publications
3
105
0
Order By: Relevance
“…Prior studies have suggested that the L452R mutation may stabilize the interaction between the spike protein and its human ACE2 receptor and thereby increase infectivity (Chen et al, 2020;Teng et al, 2021). Our findings of enhanced infection of 293T cells and lung organoids by pseudoviruses carrying L452R confirm these early predictions.…”
Section: Discussionsupporting
confidence: 87%
“…Prior studies have suggested that the L452R mutation may stabilize the interaction between the spike protein and its human ACE2 receptor and thereby increase infectivity (Chen et al, 2020;Teng et al, 2021). Our findings of enhanced infection of 293T cells and lung organoids by pseudoviruses carrying L452R confirm these early predictions.…”
Section: Discussionsupporting
confidence: 87%
“…Despite the relation between D614G and transmissibility, severity or mortality remains unclear (Grubaugh et al, 2020), different studies have suggested different implications in transmission and immune response (Teng et al, 2020;Zhang et al, 2020), but analytical and epidemiological factors could explain this observation. In patients, D614G has been associated with higher viral loads, but without significant changes of the disease severity (Korber et al, 2020;Plante et al, 2020) or vaccine effectiveness (Plante et al, 2020;Zhang et al, 2020).…”
Section: Spike Protein -D614gmentioning
confidence: 99%
“…Although strong relationships between specific variants or clades in SARS-CoV-2 and the clinical outcome have not been identified (Grubaugh, Hanage, & Rasmussen, 2020;Hodcroft et al, 2020;van Dorp et al, 2020), different relevant parameters could be impacted by mutations in the virus genome. These include transmissibility, severity, clinical management, mortality, vaccines as well as the performance of molecular tests for diagnosis (Hodcroft et al, 2020;Koyama, Platt, & Parida, 2020;Teng, Sobitan, Rhoades, Liu, & Tang, 2020). Until now, genetic factors and, more importantly, comorbidities of the host seem to have the predominant impact on the fate of COVID-19 patients (LoPresti, Beck, Duggal, Cummings, & Solomon, 2020;Sironi et al, 2020;Toyoshima, Nemoto, Matsumoto, Nakamura, & Kiyotani, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…were associated with the binding affinity of RBD. 30,31 Additionally, the mutation L5F in the signal peptide was present in 3.3% of members belonging clade V. 27 Other changes associated to relevant functions 27,30 The evolutionary rate of S protein estimated for all together clades was significantly higher than that previously reported by analyzing the entire genome. 14,28 This is expected as the complete…”
mentioning
confidence: 77%